A first assessment of genetic variability in the longhorn beetle Rosalia alpina (Coleoptera: Cerambycidae) from the Italian Apennines. Issue 1 (1st January 2018) - Molfini, M.; Redolfi de Zan, L.; Campanaro, A.; Rossi de Gasperis, S.; Mosconi, F.; Chiari, S.; Cini, A.; Antonini, G.; Solano, E.; Audisio, P. A.; Roversi, P. F.; Sabbatini Peverieri, G.; et al.
Abstract: The Rosalia longicorn ( Rosalia alpina ) is a strictly protected saproxylic beetle, widely distributed in Central and Southern Europe and mainly associated with ancient beech forests. To improve knowledge about the conservation status of R. alpina in Italy, available molecular markers (microsatellites and mitochondrial cytochrome c oxidase I(COI)) were tested for the first time on Italian populations. The study was performed in four sampling sites distributed in two areas placed in Northern ("Foreste Casentinesi" National Park) and Central Apennines ("Abruzzo, Lazio and Molise" National Park) where populational data about Rosalia longicorn were collected in the framework of the European LIFE MIPP Project. The genetic relationship among Apennine and Central/South-eastern European populations was explored by a comparison with mitochondrial DNA (mtDNA) data from literature. Microsatellite markers were only partially informative when applied to R. alpina Italian individuals, although providing some preliminary indication on an extensive gene flow among populations from the Apennines and local ongoing processes of genetic erosion. Genetic data are consistent with previous ecological data suggesting that the maintenance of variability in this species could be related to both habitat continuity and preservation of large senescent or standing dead trees in forests. Finally, a peculiar origin of the Apennine populations of R. alpina from a putative "Glacial Refugium" in Italy was inferred through COI data. The high genetic distance scored among the analysed populations and those from Central and South-eastern Europe indicates that the R. alpina deme from Apennine Mountains might represent a relevant conservation unit in Europe. Further genetic analyses will allow assessing other possible conservation units of R. alpina and, thus, defining large-scale conservation strategies to protect this endangered longhorn beetle in Europe.